Kajian Literatur : Problematika Implementasi Kurikulum Merdeka Belajar pada Pembelajaran Matematika di Sekolah Menengah - Armelia Suryaputri; Julia Ningsih; Marpaulima Aulia Sari; Rena Revita (Lembaga Pengembangan Kinerja Dosen, 2025)
This article discusses the challenges of implementing the Merdeka Learning Curriculum in mathematics education at secondary schools. The study aims to identify the obstacles faced by educators in applying this curriculum, including teacher readiness, infrastructure, and project-based learning methods. Through literature review, it was found that many teachers struggle to understand the new curriculum concepts and access digital learning platforms. Additionally, limitations in facilities and government policies deemed overly prescriptive also pose significant hurdles. Nevertheless, the Merdeka Curriculum offers opportunities to enhance educational quality through a more flexible approach. This research provides recommendations for evaluation and increased training for teachers to support more effective implementation. The findings are expected to serve as a reference for educators and policymakers in optimizing the application of the Merdeka Curriculum in Indonesia.